2017
DOI: 10.3906/biy-1606-10
|View full text |Cite
|
Sign up to set email alerts
|

Converted carotenoid production in Dunaliella salina by using cyclization inhibitors 2-methylimidazole and 3-amino-1,2,4-triazole

Abstract: IntroductionCarotenoids are the group of accessory pigments helping photosynthesis by absorbing light energy from sunlight at certain wavelengths. Their colorful feature and antioxidant properties make them commercially attractive for the biotechnology industry. As photosynthetic organisms, microalgae are a valuable natural source for carotenoid production. One of the well-known species of green microalgae is Dunaliella salina, showing the ability to produce high amounts of natural β-carotene in its unicell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…From the biotechnological perspective, a number of chemical inhibitors have been tested to regulate the carotenoid biosynthetic pathway in microalgae. For examples, Yildirim et al [24] studied the effect of the addition of 2-methylimidazole in Dunaliella salina and found an increase of 1.7-fold lutein content and a related decline in β-carotene content. This study suggested that 2-methylimidazole preferentially alters lycopene β-cyclase (lcy-b) activity and thus, shifts the carotenogenic pathway from β-carotene to the α-carotene branch.…”
Section: Putative Biosynthetic Pathway Of Lutein In Microalgaementioning
confidence: 99%
“…From the biotechnological perspective, a number of chemical inhibitors have been tested to regulate the carotenoid biosynthetic pathway in microalgae. For examples, Yildirim et al [24] studied the effect of the addition of 2-methylimidazole in Dunaliella salina and found an increase of 1.7-fold lutein content and a related decline in β-carotene content. This study suggested that 2-methylimidazole preferentially alters lycopene β-cyclase (lcy-b) activity and thus, shifts the carotenogenic pathway from β-carotene to the α-carotene branch.…”
Section: Putative Biosynthetic Pathway Of Lutein In Microalgaementioning
confidence: 99%
“…A recent study however demonstrated the modified carotenoid production pathways in Dunaliella salina by using cyclization inhibitors 2-methylimidazole (2MI) and 3-amino-1,2,4-triazole (Amitrol). The study found that 2MI was effective in lutein accumulation without affecting cell viability of D. salina when grown at high temperature [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Certain chemical inhibitors such as imidazole, pyridine, triethylamine, piperidine, nicotinic acid and nicotine, modify the carotenoids pathway to form specific products in microalgae. Yildirim et al, 2017 suggested that lutein biosynthesis in microalga can be enhanced by adding native biosynthetic pathways inhibitors. In this regard, they used 2methylimidazole (2MI) during the cultivation of Dunaliella salina to inhibit the cyclization reactions in the biosynthesis pathway carotenoids (Yildirim et al, 2017).…”
Section: Use Of Chemical Inhibitors To Enhance the Lutein Content In ...mentioning
confidence: 99%
“…Yildirim et al, 2017 suggested that lutein biosynthesis in microalga can be enhanced by adding native biosynthetic pathways inhibitors. In this regard, they used 2methylimidazole (2MI) during the cultivation of Dunaliella salina to inhibit the cyclization reactions in the biosynthesis pathway carotenoids (Yildirim et al, 2017). The addition of 2MI at a concentration of 1 mM enhanced the lutein content by 1.7folds with a simultaneous reduction in b-carotene content, hence proving that 2MI affects the activity of lycopene bcyclase (LCY-b) that is responsible for a-carotene synthesis (Yildirim et al, 2017).…”
Section: Use Of Chemical Inhibitors To Enhance the Lutein Content In ...mentioning
confidence: 99%
See 1 more Smart Citation